Interpretations to the places of the Poem of Parmenides on Heidegger’s path to the "Thinkers of the Beginning" - Díaz Arroyo, José Luis (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2021)
Some contrasts will be shown around the places of the notion of selfhood in Poem of Parmenides between various texts by Martin Heidegger, with particular attention to what the forgetfulness of Parmenides' “word enigma” has in Sein und Zeit to have to do with the notion of Self elaborated there. Through the path to the “thinkers of the beginning”, distinguishing the questioning horizon of Plato’s dialogue from that of the Parmenides' Poem will lead us in turn to point out the different ways in which Heidegger thinks the same in the Parmenides' Poem.